(untitled) (The Research of Medical Science Review, 2025)
Honor killing continues to be rooted as a gender violence, largely hidden behind family silence, cultural alibi, and legal ambivalence. The present study reports a thorough forensic analysis of an intra-family murder in Pakistan, where a 16-year-old female was killed by her brother on the excuse of upholding family "honor." Conducted with a multidisciplinary forensic pathway, the analysis involved careful management of the crime scene, collection of biological traces, ballistic analysis, gunshot residue (GSR) analysis, DNA typing, and medico-legal autopsy. The autopsy determined the cause of death to be hemorrhagic shock due to a close-range gunshot wound to the heart and left lung. Sexual assault was not observed. Ballistic examination detected the bullet casing with recovered 30-bore pistol, and analysis for GSR confirmed recent discharge of firearm by the accused. Even after the accused's tearful admission, forensic reports yielded conclusive evidence, and there was a conviction in terms of Section 302 of the Pakistan Penal Code. The case shows the pivotal role forensic science plays in overcoming challenges in honor crimes. It lays stress upon the fact that objective, fact-based inquiries are necessary in shattering impunity chains of domestic killings in culturally delicate cases and in providing justice to the victims where customary norms may bar legal accountability. Key Words : Honor killing, forensic examination, family homicide, cultural violence, crime scene reconstruction, forensic pathology, gender violence, legal responsibility, case-based justice, forensic anthropology, bloodstain pattern analysis, motive analysis, forensic ethics, victimology.